The moral foundations of the youth justice system: understanding the principles of the youth justice system - Arthur, Raymond (Routledge, Taylor & Francis Group, 2017)
Introduction -- The origins of childhood and the youth justice system -- New labour, new youth justice, new century -- The impact of international law -- Young people who offend -- Impact of criminalisation -- Young people, the youth court and the right to a fair trial -- The youth justice system and theories of punishment -- Conclusions